If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 53 = 10x + 13 Reorder the terms: 53 + 6x = 10x + 13 Reorder the terms: 53 + 6x = 13 + 10x Solving 53 + 6x = 13 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 53 + 6x + -10x = 13 + 10x + -10x Combine like terms: 6x + -10x = -4x 53 + -4x = 13 + 10x + -10x Combine like terms: 10x + -10x = 0 53 + -4x = 13 + 0 53 + -4x = 13 Add '-53' to each side of the equation. 53 + -53 + -4x = 13 + -53 Combine like terms: 53 + -53 = 0 0 + -4x = 13 + -53 -4x = 13 + -53 Combine like terms: 13 + -53 = -40 -4x = -40 Divide each side by '-4'. x = 10 Simplifying x = 10
| w^3=1 | | x+4=2(2x-10) | | x+4=2(x-10) | | 2x+12=3+4x-7 | | 1218=x+(x+10) | | 1000=x+(x+10) | | 1000=x+(x+10)*y | | omega^3=1 | | 3x-17=8x-5(x-2) | | tan*cos=sin | | 3(x-1)+6=3x+2 | | 2(x+3)+x=3x+6 | | tang*cos=sin | | 5(x-1)=4x-2 | | 3x+12+x=4x+12 | | 6x-8=9-2x+5-3x | | 4-2x+6=3x+10 | | 2-2x+5=2x+10-2 | | x^4+4x^3-3x^2-12x=0 | | 2x=(3x-3)(m+4) | | 3X^2-200X+3125=0 | | 2(x-a)+b=3x+a | | x^3-100x^2+3125x=0 | | 3x=108 | | 11(x+4)-3x=2(4x+3)-12 | | 13x-5=4(3x+2)-3 | | 1.5x+8x=3x+117 | | 4[9-(-6x-8)]=72x+132 | | -5x+x^2=-25 | | -.75m+3=-12 | | -25+-25= | | 8x=7x-5 |